Pengaruh Kepemilikan Keluarga dan Likuiditas terhadap Agresivitas Pajak dengan Pemoderasi Corporate Governance - Anggi Aditya Fahmi; Priyo Hari Adi (Center for Accounting Development and Research (CARD) Program Studi Akuntansi – Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
The purpose of this study is to find out how the influence of companies with family ownership and liquidity on tax aggressiveness which is moderated by corporate governance in manufacturing companies listed on the Indonesia Stock Exchange from 2013 to 2016. Corporate governance is proxied using independent commissioners and audit committees. The sample used in this study amounted to 212 selected using the purposive sampling method. The data analysis technique used are moderated regression analysis (MRA). The results showed that family ownership did not affect the tax aggressiveness, this means that companies with family ownership do not determine the company's actions in conducting tax aggressiveness. Liquidity has a significant positive effect on tax aggressiveness. The moderating variable of independent commissioners can moderate the influence of family ownership and liquidity on tax aggressiveness, while the moderating variable of the audit committee can moderate liquidity but cannot moderate family ownership against tax aggressiveness.